“Menggugat” Putusan Mahkamah Konstitusi Nomor 46/PUU-XIV/2016 - Wira Atma Hajri; Rahdiansyah Rahdiansyah (Jurnal Selat, 2022)
Through Decision Number 46/PUU-XIV/2016, the Constitutional Court affirms that the Constitutional Court is not authorized to extend a legal norm or create a new norm, even though the tested norm is related to the blessing of this nation, namely adultery. Therefore, this research aims to determine whether or not the Constitutional Court can form a new norm in cases of judicial review. This research is a legal search that uses a statutory approach, a sociological approach, a historical approach, a conceptual approach, and a comparative approach. The Constitutional Court can form new norms for several reasons, namely the existence of the Constitutional Court Decision Number 48/PUU-IX/2011 which cancels articles regarding the prohibition of the Constitutional Court to form new norms, legal politics of judicial power in Indonesia, the need for law in society, and the practice that has occurred so far in which the Constitutional Court has several times established new norms. However, the most important reason is the existence of Article 29 Paragraph 1 of the 1945 Constitution as the main basis for the state to state that the State is based on One Godhead. The consequence is that things that smell of immorality must not be allowed to live in Indonesia. Disobedience certainly brings anger from Allah.